Measurement of vapor viscosity of R1234yf and its binary mixtures with R32, R125. (October 2015) - Dang, Yagu; Kim, Hong Seok; Dang, Chaobin; Hihara, Eiji
Abstract: The vapor viscosities of the new refrigerant R1234yf and its binary mixtures, R32+R1234yf, R125+R1234yf, were measured at atmospheric pressure with a falling-ball-type viscometer. The combined expanded uncertainty of the measurement apparatus was less than 1.5%. The binary mixtures consisted of 20.0, 30.0, 40.0, and 50.0 wt% R32 for R32+R1234yf and of 20.0, 35.0, 50.0, and 70.0 wt% R125 for R125+R1234yf. The viscosities of R1234yf were correlated with the Chapman–Enskog gas kinetic theory and those of binary mixtures were correlated with the Wilke mixture rule. The average absolute deviation (AAD) is 0.189% for R32+R1234yf and 1.169% for R125+R1234yf. The deviations of experimental viscosities of the binary mixtures from data calculated using RefProp v9.1 were also obtained. The AAD is 0.555% for R32+R1234yf and 1.479% for R125+R1234yf. Highlights: The vapor viscosities of R1234yf and R32+R1234yf, R125+R1234yf were measured. Viscosity was measured at atmospheric pressure with a falling-ball-type viscometer. R1234yf viscosity was modeled using the kinetic theory, with an AAD of 0.357%. Viscosities of R1234yf mixtures were correlated with the Wilke mixtures rule.